2016
DOI: 10.1542/peds.2015-4268l
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Adverse Childhood Experiences and Risk of Cancer in Adulthood: A Systematic Review of the Literature

Abstract: CONTEXT Adverse childhood experiences (ACEs) can affect health and well-being across the life course. OBJECTIVE This systematic review summarizes the literature on associations between ACEs and risk of cancer in adulthood. DATA SOURCES We searched PubMed to identify relevant publications published on or before May 31, 2015. STUDY SELECTION We included original research quantifying the association between ACEs and adult cancer incidence. Case reports and reviews were excluded. DATA ABSTRACTION Two revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 43 publications
1
116
1
2
Order By: Relevance
“…This is important because, in non-cancer populations, intervention studies targeting some psychological resources have proven to be ineffective, such as those targeting self-esteem (Baumeister, Campbell, Krueger, & Vohs, 2003), and individuals with a trauma history may benefit from different types of treatment than those without (Lewis et al, 2010; Nanni et al, 2012; Weisz, McCarty, & Valeri, 2006). Childhood maltreatment may predispose individuals to cancer (Holman et al, 2016), and is associated with earlier all-cause mortality (Chen, Turiano, Mroczek, & Miller, 2016). Identifying key psychological pathways from childhood maltreatment to psychopathology that are responsive to interventions is essential to mitigating the lifelong health disparities associated with childhood maltreatment exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because, in non-cancer populations, intervention studies targeting some psychological resources have proven to be ineffective, such as those targeting self-esteem (Baumeister, Campbell, Krueger, & Vohs, 2003), and individuals with a trauma history may benefit from different types of treatment than those without (Lewis et al, 2010; Nanni et al, 2012; Weisz, McCarty, & Valeri, 2006). Childhood maltreatment may predispose individuals to cancer (Holman et al, 2016), and is associated with earlier all-cause mortality (Chen, Turiano, Mroczek, & Miller, 2016). Identifying key psychological pathways from childhood maltreatment to psychopathology that are responsive to interventions is essential to mitigating the lifelong health disparities associated with childhood maltreatment exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 66% of U.S. adults report at least 1 ACE during childhood, and 20% report 4 or more. ACEs are associated with increased risk of chronic diseases and early death in adulthood, and have been estimated to cost billions of dollars in direct medical expenses and work‐related absenteeism . Headaches are a potential physical manifestation of ACEs, and several studies have shown a relationship between ACEs and headache disorders, including migraine, among adults .…”
Section: Introductionmentioning
confidence: 99%
“…ACEs are associated with increased risk of chronic diseases and early death in adulthood, and have been estimated to cost billions of dollars in direct medical expenses and work-related absenteeism. [1][2][3][4][5][6] Headaches are a potential physical manifestation of ACEs, and several studies have shown a relationship between ACEs and headache disorders, including migraine, among adults. 1,[7][8][9][10][11][12] Numerous pathophysiological theories have been suggested to explain the association between ACEs and headaches, including depression and anxiety, which are common comorbidities in patients with headaches and were found to be associated withACEs.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that ACEs are a major contributor to morbidity and mortality in adults with dose-response relationships between the number of ACEs and chronic diseases. 5,32 With the strong relationship between ACEs, toxic stress, and adverse health outcomes, the question arises as to how the LLBZ community members, especially the centenarians, are able to achieve such resilient longevity despite enduring tremendous childhood adversity.…”
Section: Original Research and Contributions Adverse Childhood Experienmentioning
confidence: 99%